DIFERENSI SOSIAL DALAM MASYARAKAT: KAJIAN TERHADAP BENTUK DAN DAMPAKNYA TERHADAP INTERAKSI SOSIAL - Muhammad Adafi Al Akbar (Jurnal Sosiologi UPR, 2025)
Social diversity is the main characteristic of a pluralistic Indonesian society. Social differentiation as a form of horizontal difference is the basis of the plurality of society consisting of various racial, ethnic, religious, gender, and professional groups. This study aims to identify forms of social differentiation and evaluate their impact on social interaction patterns, both integrative and disintegrative. The study was conducted using a descriptive qualitative approach through a literature review of various scientific sources and empirical studies. The results of the analysis show that social differentiation can enrich social structures and strengthen solidarity if managed fairly, equally, and inclusively. However, if not accompanied by tolerance and recognition of sociocultural rights, this differentiation has the potential to cause conflict between groups. Therefore, critical understanding and policies that support equality are needed to strengthen social cohesion.